Superprotonic conductivity in flexible porous covalent organic framework membranes - Banerjee, Rahul; Sasmal, Himadri Sekhar; Harshitha, B. A.; Bhange, Siddheshwar; Karak, Suvendu; Halder, Arjun; Kurungot, Sreekumar (Angewandte Chemie, 2018)
Poor mechanical stability of the polymer electrolyte membranes (PEMs) remains one of the bottlenecks towards improving the performance of the proton exchange membrane (PEM) fuel cells. The present work proposes a unique way to utilize crystalline covalent organic frameworks (COFs) as a self‐standing, highly flexible membrane to further boost the mechanical stability of the material without compromising its innate structural characteristics. The as‐synthesized p‐toluene sulfonic acid loaded covalent organic framework membranes (COFMs) showing the highest proton conductivity amongst all crystalline porous organic polymeric materials reported till date, as high as 7.8 x 10‐2 S cm‐1, have been further tested under real PEM operating conditions to ascertain their practical utilization as proton exchange membranes. Attainment of 24 mW cm‐2 power density, which is the highest among COFs and MOFs, highlights the possibilityof using a COF membrane over the other state‐of‐the‐art crystalline porous polymeric materials reported to date.